PENGARUH KEPEMIMPINAN, KEMAMPUAN DAN MOTIVASI DIRI TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN SINGOSARI KABUPATEN MALANG - Rohmad, Rohmad; Suswati, Endang; Srihadiyati, Srihadiyati (Manajemen & Bisnis Jurnal, 2020)
Abstract, The Effect of Leadership, Ability and Self-Motivation on VillagePerformance in Singosari District, Malang Regency. Government in the villagearea is an organization consisting of people who have a series of activities that areclear and carried out continuously to achieve organizational goals and this can berealized optimally if supported by the performance of village officials.Theobjectives of this study are: 1) To test and analyze leadership, ability, selfmotivation and performance of village officials 2) To test and analyze leadership,ability and self motivation simultaneously influence the performance of villageofficials 3) To test and analyze leadership, ability and self motivation partiallyinfluences the performance of village officials 4) To test and analyze the dominantinfluence between leadership, ability and self motivation on the performance ofvillage officials.This type of research is explanatory research, which explains thecausal relationship between research variables through hypothesis testing. Thepopulation used in this study is the village apparatus in Singosari District MalangRegency as many as 156 village apparatuses with a total sample of 61 respondents.The data analysis technique used in this study is multiple linear regressionanalysis.The results of the analysis show that leadership in Singosari DistrictMalang Regency is included in the good category, high employee ability, highemployee motivation and performance of village officials in Singosari DistrictMalang Regency included in the high category. There is an influence of leadership,ability and work motivation on the performance of village officials in SingosariDistrict, Malang Regency. Based on Beta Standardized Coeficients, workmotivation variables have a dominant influence on village officials in SingosariDistrict, Malang Regency.Keywords: Leadership, Ability, Self Motivation and Performance of VillageOfficials